Prospects and Challenges of Generic Medicines Adoption in India: Consumer and Physician Perspectives: Pharmaceutical Science-Pharma - Chattoraj, Abhijit; Pareek, Manoj; Thomas, Becky; Doss, Steward (International Journal of Life Science and Pharma Research, 2022)
The objective of this study was to learn more about consumers’ and physicians’ knowledge, attitudes, and beliefs about generic medicines, as well as the problems in guaranteeing generic medicine acceptance and utilization. The aim of our study was to figure out what would improve physician acceptance and customer acceptance. The study included qualitative research with focus group conversations with physicians from various fields of medicine, as well as a cross-sectional survey with 102 customers in Pune divided into two clusters utilizing a questionnaire. An exploratory factor analysis was performed to see if there were any differences between the components, that support favorable opinions of Generic Medicines and those that support negative perceptions of the same. Customers were positive, about the usage of generic drugs according to the findings. The findings showed a preference to use them on doctor’s prescriptions and Government or other regulatory agencies approval. Physicians also proposed that the government should make it mandatory for generic medicines to be prescribed by doctors and launch a robust public awareness campaign to encourage their use in India. There was an acceptance that, using generic medicine would significantly lower healthcare expenses. The physicians believed that generic bioavailability and bioequivalence were important factors to consider when deciding whether or not to prescribe generics. Clinical trial data and serious adverse event (SAE) data, should also be made available to the medical community so that transparent and independent decisions can be made.